Students Strategies In English Vocabulary Learning - Yunia Dwi Ningtyas; Calista Dyah Octavia; Rizka Anis Fuadillah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The vocabulary is an important elemen in English mastery. Limited vocabulary willprevent student from communitation in English. The importance of vocabulary in languagelearning is also illustrated by Mr. Wilkins (thorn bury, 2003:13), stating that “withoutvocabbbulary, nothing can be stressed; without vocabulary, nothing can be bulletproof ‘.Futher he posses that by studying a vocabulary one will be able radiply improvinglanguage ability. There fore need ti implement appropriate learning strategies. There areseveral learning strategies such as the TPR method, learning by song, learning by planand so on. Vocabulary is really important to learn. Without grammar, little can beconveyed, but without vocabulary nothing can be conveyed.